Determination and Assessment of Places at Risk of Desertification Using Geoinformation Technologies - Nuriddinov Otabek Khurramovich; Jurayev Qurbon Hafiz ugli; Qo’ziyev Xonnazar Zoyir o’g’li- (Zien Journals, 2022)
This article is aimed at determining the global environmental problems of land protection from desertification and the areas in need of planning measures for the prevention of desertification, that is, determining and assessing the level of the risk of land degradation.
Keywords: desertification; deflation; water bodies; decoding